Comparative genomic analysis of emerging non-typeable Haemophilus influenzae (NTHi) causing emerging septic arthritis in Atlanta - Bixler, Brianna J.; Royer, Charlotte J.; Petit III, Robert A.; Moller, Abraham G.; Sefton, Samantha; Thomas, Stepy; Tunali, Amy; Collins, Lauren F.; Farley, Monica M.; Satola, Sarah W.; Read, Timothy D. (PeerJ (San Francisco, CA), 2025)
is a Gram-negative bacterium that can exist as a commensal organism or cause a range of diseases, from ear infections to invasive conditions like meningitis. While encapsulated strains have historically been linked to severe diseases, non-typeable (NTHi) strains, lacking an intact capsule locus, have emerged as the leading cause of invasive infections, particularly following the widespread use of the serotype b (Hib) vaccine. In response to a significant increase in invasive NTHi infections among persons living with HIV in metropolitan Atlanta during 2017-2018, we conducted a comparative genomic analysis of two predominant NTHi clones, C1 and C2, identified during this period. These clones correspond to multilocus sequence types ST164 and ST1714, respectively. We analyzed the genomic characteristics of C1 and C2 using whole genome sequencing data and compared them to a broader pangenome of strains to identify potential virulence factors and genetic adaptations. Both C1 and C2 isolates were highly related within their clusters, with C1 showing a maximum of 132 SNPs and C2 showing 149 SNPs within their respective core genomes. Genomic analysis revealed significant deletions in known virulence genes, surprisingly suggesting possible attenuation of virulence. No unique accessory genes were identified that distinguished C1 and C2 from other strains, although both clusters exhibited a consistent loss of the gene (encoding 5-oxoprolinase subunit), replaced by a mobile cassette containing genes potentially involved in sugar metabolism. All C1 and C2 isolates showed potential enrichment in accessory genes associated with systemic infections. Our study suggests that while C1 and C2 clones possess some genetic markers potentially linked to systemic infections, there are no definitive unique genetic factors that distinguish these clones as more virulent than other strains. The expansion of these clones in a vulnerable population may reflect both chance introduction and potential adaptations to the host environment. Further research is needed to understand the implications of these genetic findings on the clinical management and prevention of invasive NTHi infections.